2017
DOI: 10.1039/c7ra07157d
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient UV-sensing properties of Sb-doped ZnO nanorod arrays synthesized by a facile, single-step hydrothermal reaction

Abstract: The synthesis of electrical and optical property-modulated, low-dimensional metal oxide semiconductors has been adopted for the development of nanodevices. However, conventional modulation methods, such as doping and alloying, generally require rather complex processes, such as multi-step high-temperature reactions, gas-phase growth, high-vacuum processes, etc. Alternatively, in the current study, the facile and cost-effective synthesis of Sb-doped ZnO nanorod arrays (NRAs) is achieved using a simple hydrother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…V O defect generates free electrons in the system that bound to adsorbed oxygen molecule generating an electronic depletion layer. Thus, ZnO nanorods surface absorb more oxygen molecule in the air due to more free electrons generated by V O leading to enhancement of electronic depletion layer . This enhancement plays an important role in scattering/trapping centers for conduction electrons that suppress the amount of dark current .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…V O defect generates free electrons in the system that bound to adsorbed oxygen molecule generating an electronic depletion layer. Thus, ZnO nanorods surface absorb more oxygen molecule in the air due to more free electrons generated by V O leading to enhancement of electronic depletion layer . This enhancement plays an important role in scattering/trapping centers for conduction electrons that suppress the amount of dark current .…”
Section: Resultsmentioning
confidence: 99%
“…Under illumination of light, the electron–hole pairs are generated in the system, this hole recombines with the electron bound to oxygen molecules, which leads to the oxygen desorption process on the surface of the nanorods. This process induces to the decrease of electronic depletion layer and the conductivity will increase . From the schematic diagram, it can be clearly seen that for the case of ZnO nanorods MSM photodetector the amount of nanorods which contributes to the absorption and desorption process of oxygen molecule is much higher than that of p‐n heterojunction.…”
Section: Resultsmentioning
confidence: 99%
“…Many endeavored research works have been recently conducted for achieving ZnO with p‐type conductivity by doping ZnO with group I and versus elements such as Li, Na, K, N, P, As, and antimony (Sb). [ 8–14 ] Sb is among potential candidates to achieve p‐type ZnO because of a relatively heavy element compared with zinc and oxygen and good acceptor behavior. [ 15 ] It has been reported that p‐type conductivity in Sb‐doped ZnO can be achieved by Sb substitution at Zn site resulting chemical bonding with two zinc vacancies (Sb Zn –2V Zn ), then forming acceptor complex in ZnO.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO exhibits wide bandgap of 3.37 eV, large exciton binding energy of 60 meV at ambient temperature, excellent transparency, low production cost, non-toxicity, and good stability (Sang et al, 2018;Zhang et al, 2016;Samavati et al, 2017;Li et al, 2015;Shaban et al, 2018;Stehr et al, 2015). The main applications of zinc oxide include solar cells, light-emitting diodes, laser diodes, piezoelectric devices, photosensors, thin-film transistors, auto-heaters, paints, antibacterial agents, biosensors, gas sensors, and photocatalysts (Mudusu et al, 2016;Park et al, 2015;Akhtarianfar et al, 2017;Gupta et al, 2016;Yu et al, 2016 ;Wu et al, 2016;Rajendran et al, 2016;Kim et al, 2017;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%